2021
DOI: 10.1111/aej.12599
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dual rinse irrigation on dentinal penetration of a bioceramic root canal sealer: A Conofocal microscopic Analysis

Abstract: To evaluate the sealer penetration after applying dual rinse irrigant in comparison with sodium hypochlorite and 17% EDTA. Mandibular premolars were prepared by ProTaper Next and irrigated with NaOCl, NaOCl/Dual Rinse or NaOCl/EDTA and then obturated with a single‐cone technique and bioceramic‐based. Samples were observed using confocal laser microscopy, and the maximum depth of penetration was measured, as well as the percentage of sealer coating the canal wall and the penetration area of the sealer. One‐way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Although Generali et al 15 found no difference in sealer penetration at different levels, most likely because a chelating agent was used, 10 the results of this study were found in agreement with results from McMichael et al 16 and El Hachem R 17 , who found that the BC Sealer penetration depth was significantly higher at the coronal and middle levels compared to the apical ones.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Although Generali et al 15 found no difference in sealer penetration at different levels, most likely because a chelating agent was used, 10 the results of this study were found in agreement with results from McMichael et al 16 and El Hachem R 17 , who found that the BC Sealer penetration depth was significantly higher at the coronal and middle levels compared to the apical ones.…”
Section: Resultssupporting
confidence: 90%
“…The total area with sealer penetration was delineated and measured by subtracting the root canal space from the entire area of the sealer penetration in square micrometers (µm 2 ) 10 . The percentage of sealer penetration (%) was calculated by the division of the area of sealer penetration by the circumference of the root canal wall.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The study concluded that Group (NaOCl/Dual Rinse) displayed better sealer penetration inside the dentinal tubules than Group (NaOCl/EDTA), while Group (NaOCl) showed the lowest sealer penetration. 33 …”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] The sealer penetration area was calculated by subtracting the amount of root canal space from the total area of the sealer penetration. 16,17 Statistical analysis: Statistical evaluation was performed using the statistical software SPSS (version 23, IBM Co. USA). The Shapiro-Wilk test was used for testing the normality of data.…”
Section: Introductionmentioning
confidence: 99%